“Atención psicológica y autoestima. Estudio en el centro de educación básica “Nicanor Larrea”. Riobamba. Chimborazo. período diciembre 2015- junio 2016”. - Maliza Guanulema, Paola Alexandra (2017)
The present thesis it announces the psychological attention and self-esteem. This study in the was in "Nicanor Larrea". Riobamba. Chimborazo. Period December 2015-June 2016; which has for aim to demonstrate how the suitable Psychological attention raises the self-esteem in children of 5th year of basic education in Dr. Nicanor Larrea elementary school during the period 2015-2016. For it treated itself of he identifies the type of Psychological Attention that is offered to the students on the part of the counselor since one can be observed without number of difficulties; It is important to establish the level of self-esteem of children to identify the problems that happen in the institution. During all this process were observed many situations in which the main beneficiaries were the students, which we share and work using group and individual work with the aim to gain information in order to analyze, interpret and get good results. The methodology was inductive-deductive it means clear and simple specifically to students in Nicanor Larrea elementary school, sections A, B, C; with a final number of one hundred seventeen students. To data collection, the self-esteem A.EP test for primary education is applied and the observation sheet consists of seven questions for the counselor. Upon culminating with all this work the results were tabulated, analyzed and interpreted according to the results obtained in the research; Which was concluded is very important the contribution of the student oriented for its development in the educational context.